The prediction Model of OCD personality based on complex trauma and object relation with mediating role of ego strength in conflicting couples - Bayani, Bita; Jafari, Asghar; Shafie Abadi, Abdollah; Hoseinian, Simin (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to study the predicting model of borderline personality based on complex trauma and object relation with mediating role of ego strength in conflicting couples. Methods: Method was descriptive-correlational. Population was all refereeing couples to counseling and psychological clinics in 2021 in Tehran. Using multi cluster sampling and cutting point >75 in MCMI-3, 205 participants with borderline and inclusion criteria were selected and completed the questionnaires of Markstorm and et al, s (1997) PIES, Milon-3, s (1997) MCMI-3, Bell’s (1995) BORI, Borneshtian & et al, s (2003) CTQ. Data were analyzed by Pearson correlation and SEM. Findings: There is a positive and significant relationship between trauma and borderline and there is a negative and significant relationship between ego strength and borderline (p<0.01). The results of SEM showed that the prediction Model of borderline based on complex trauma and object relation with mediating role of ego strength is fit (p<0.01). Conclusion: Ego strength effect on borderline through moderating object relation and effacing the dimension of cognitive and emotional of childhood trauma. Therefore, it was suggested, pay attention to trauma, object relation in etiology and therapy of borderline, and promote ego strength by training and counseling.